PERUBAHAN WARNA BERCAK DARAH PADA MANUSIA DEWASA DENGAN KADAR HEMOGLOBIN DI BAWAH NORMAL BERDASARKAN KARTU STANDAR WARNA NATURAL COLOR SYSTEM (NCS) - Fitra Afdanil; Mohammad Tegar Indrayana; Fridayenti " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
On the crime scene, the forensic medicine was important to express a murder case with investigation procses that did on occurance’s place. There are many exhibit that was found, one of the exhibit is blood stain. Blood stain has useful on investigation procses, firstly to estimate the time on occurance of murder. The purpose of this research was to know the change of blood stain’s color on adult human that has subnormal hemoglobin with color’s card standart NCS. This research was happened on may 2014 with deskriptive method and Cross Sectional approach on 31 patient mans and woman’s adults with subnormal hemoglobin in RSUD Arifin Achmad Pekanbaru. Based on 31 sample was get the color’s change from the blood stain with subnormal hemoglobin occurance on 1st until 6th clock, while on 7th until 48th there are was not occurance of the color’s change from the blood stain.Key words : Blood stain, color change, subnormal hemoglobin, color card NCS